2012
DOI: 10.3390/molecules171213864
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Preparation of α-Ketoacetals

Abstract: The Weinreb amides 2a,b were prepared from the α,α-dimethoxyacetic acids 1c,d. A number of representative nucleophilic additions (RMgX and RLi) on 2 afforded α-ketoacetals 3a–j in 70–99% yield. These compounds represent a versatile arrangement of functional groups of significant synthetic value, as demonstrated in the synthesis of (±)-salbutamol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Zepeda et al showed that salbutamol can be obtained by reacting acetal 7.2.a with t BuNH 2 in the presence of sodium borohydride (Scheme ). As a result, salbutamol was obtained in 81% yield (85 mg of the product, 11% RME).…”
Section: Drugs Affecting the Respiratory Systemmentioning
confidence: 99%
“…Zepeda et al showed that salbutamol can be obtained by reacting acetal 7.2.a with t BuNH 2 in the presence of sodium borohydride (Scheme ). As a result, salbutamol was obtained in 81% yield (85 mg of the product, 11% RME).…”
Section: Drugs Affecting the Respiratory Systemmentioning
confidence: 99%
“…7 Ayala-Mata and group employed Weinreb amides as a starting material for the synthesis of α-ketoacetals (Scheme 1b). 8 More recently, we have reported the synthesis of phenylglyoxal diethylacetals via the reaction of aromatic ketones with triethylorthoformate in the presence of H 2 SeO 3 catalyzed by BF 3 ·Et 2 O (Scheme 1c). 9 This method, though simple is limited by the use of triethylorthoformate as the sole source of alkoxide nucleophile.…”
Section: Introductionmentioning
confidence: 99%
“…For instance the α-ketoacetals are a key intermediate in the synthesis of various biological active compounds such as chiral α-hydroxy acetals, chiral α-amino acetals, chiral auxiliaries, and cyanosilylation and also for the construction of important heterocycles . Several methods have been described for the preparation of α-ketoacetals. Goswami et al, reported the synthesis of aliphatic α-ketoacetals starting from ketones via a two step procedure using SeO 2 . , Tiecco and co-workers reported the synthesis of α-ketoacetals catalyzed by diphenyldiselenide and an excess of ammonium peroxydisulfate under reflux conditions (Scheme a) . Ayala-Mata and group employed Weinreb amides as a starting material for the synthesis of α-ketoacetals (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2,4-disubstituted phenyl ring took longer time for completion (Table 3, entry 6). This reaction has a potential to generate key intermediates α,α-dimethoxy acetophenones which find application in the synthesis 15 of chiral cyanohydrins, nicotine derivatives, chiral sulfoxides, α-hydroxy acetals, chiral 1,2-diols, and myretnalderived chiral auxillaries. We have reported an unusual observation of oxidative cleavage of the C-C bond in chalcone epoxides followed by acetalization with methanol to form α,α-dimethoxyacetophenones, when chalcone epoxides are reacted with iodine in methanol.…”
mentioning
confidence: 99%